FORMATION OF THE LEADING TEACHER IN EDUCATIONAL PROCESS OF HIGHER EDUCATION INSTITUTION - I. B. Bicheva; O. M. Filatova (Вестник Мининского университета, 2017)
The publication purpose – to reveal intrinsic characteristics of the leading teacher and to develop pedagogical conditions of formation of leadership skills of students – future preschool teachers in educational process of higher education institution. Methodological principles of article are the theory of leadership and development of the personality. When carrying out a research were used the analysis of scientific-theoretical provisions of the concept "leader" of the system of modern professional and pedagogical knowledge.Content – the analysis of the studied problem has allowed authors to define that the leading teacher is a personality to whom trust and who is recognized; capable to lead group of children (parents, colleagues), awakening their activity and interest; to influence interaction process, regulating relationship; to responsibly organize performance of this or that activity. The conclusion is drawn that in the conditions of modernization of educational system the leading teacher becomes the important strategic resource of all transformations capable to generate and perceive innovations, ready to show activity and creativity.The fundamental qualities causing purposeful development of the important personal and professional characteristics leading the personality to the leader's position have defined independence and responsibility.Three groups of the pedagogical conditions in total forming special leader space, approving social, active and creative essence of the identity of students and forming qualities of the successful leading teacher are proved: reflexive and motivational, substantial and informative and activity.Authors join in structure of qualities of the leading teacher: the motivational focused, intellectual and strong-willed, behavioural, social and communicative qualities. It is shown that existence of the marked-out qualities though increases development of the teacher as leader, but possession of them not necessarily turns the individual into the leader.The theoretical provisions submitted in work supplement basic provisions of the theory of leadership, enriching the theory and a technique of continuous professional education.